2015
DOI: 10.1039/c4ra11177j
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of magnetic molecularly imprinted microspheres by RAFT precipitation polymerization for the fast and selective removal of 17β-estradiol

Abstract: A facile strategy was developed to prepare magnetic molecularly imprinted microspheres (MMIMs) for the selective recognition and effective removal of 17-beta-estradiol (17b-E2) by reversible additionfragmentation chain transfer precipitation polymerization. One-pot synthesis was employed, which could simplify the imprinting process and shorten the experimental period. The resultant MMIMs displayed fast kinetics and high binding capacity, and the adsorption processes followed LangmuirFreundlich isotherm and pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…The magnetic nanoparticle-adsorbed target compounds can be easily collected by an external magnetic field without additional centrifugation or filtration of samples [15]. Also, metal-organic frameworks (MOFs), crystalline solids consisting of metal ions coordinated by organic ligands to form rigid three dimensional frameworks, have received increasing concerns owing to their unique properties such as high surface area, high pore volume and chemical tenability [16][17][18] mg/L of chlorfenapyr dissolved in n-hexane were purchased from National Research Center for Certified Reference Materials (Beijing, China), which were all stored at -20 ºC.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic nanoparticle-adsorbed target compounds can be easily collected by an external magnetic field without additional centrifugation or filtration of samples [15]. Also, metal-organic frameworks (MOFs), crystalline solids consisting of metal ions coordinated by organic ligands to form rigid three dimensional frameworks, have received increasing concerns owing to their unique properties such as high surface area, high pore volume and chemical tenability [16][17][18] mg/L of chlorfenapyr dissolved in n-hexane were purchased from National Research Center for Certified Reference Materials (Beijing, China), which were all stored at -20 ºC.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a sensitive and faster method for the identification and quantification of such Sudan dyes in foods is required urgently. Although MMIPs developed by RAFT methodology [12,[28][29][30][31] and the separation of Sudan dyes from chilli powder by MIPs [32][33][34] are reported, the MMIP made by RAFT technology for the extraction and separation of Sudan dyes have never been reported so far.…”
Section: Introductionmentioning
confidence: 93%
“…Until now, there are some studies of molecularly imprinted polymers on estradiol have been reported [17][18][19]. Currently, there are three strategies, namely covalent, non-covalent and semicovalent imprinting, for preparing molecularly imprinted materials [20].…”
Section: Introductionmentioning
confidence: 99%